Comparison of cross-matching method for detection of DEA 7 blood incompatibility. (November 2018) - Spada, Eva; Perego, Roberta; Viñals Flórez, Luis Miguel; del Rosario Perlado Chamizo, Maria; Baggiani, Luciana; Dall'Ara, Paola; Proverbio, Daniela
We compared 3 major cross-match (XM) tests to identify dog erythrocyte antigen (DEA) 7 blood incompatibilities in dogs as a result of anti–DEA 7 antibodies: gel (GEL), standard tube (TUBE) agglutination, and immunochromatography strips (STRIP). Blood samples from 42 dogs were typed for DEA 7; 2 tested DEA 7–positive (DEA 7+). The 40 DEA 7–negative (DEA 7–) plasma samples were cross-matched against the 2 DEA 7+ and 3 DEA 7– red blood cell (RBC) samples by GEL to identify samples with anti–DEA 7 antibodies. Twenty DEA 7– plasma samples without and with anti–DEA 7 antibodies were cross-matched with samples of the 2 DEA 7+ RBCs in a double-blind fashion using the TUBE and STRIP XM methods. GEL results were used as the reference method for comparison. To determine relationships between results, 2 × 2 tables were used. Cohen kappa coefficient (κ) was calculated between results of GEL and the other 2 methods. With GEL, 21 of 40 XM tests were positive and 19 of 40 negative for anti–DEA 7 antibodies. The same results were obtained by TUBE, whereas only 1 of 40 XM tests was positive by STRIP. There was a statistically significant relationship between results of GEL and TUBE ( p < 0.000) with perfect agreement (κ = 1.000), but not between GEL and STRIP results ( p = 1.000) in which agreement was equivalent to chance (κ = 0.0453). The GEL and TUBE XM tests, but not STRIP, are useful methods for identification of DEA 7 incompatibilities caused by anti–DEA 7 antibodies.